STORAGE AS A KEY AREA OF INTEGRATED LOGISTICS (Perner's Contacts, 2011)
The reduction of trade barriers on domestic and international market has led to the rapid growth of logistics services across all business sectors. The more important became a topic of global logistics and a business in a global concept. Global business operations increase the demands on logistics as well as the efficiency. Modern logistics practice therefore tends to complex problem solving and full integration of supply chains. The target is an integrated logistics characterized by high professionalism, high degree of flexibility and is perfectly connected to all parts of business chain.
Keywords: Global logistics; Integrated logistics; Supply chain; Inventory management; Storage